The Use of Verbs in Banks’ Corporate Websites - Ricardo Casañ-Pitarch (Journal of Modern Languages)
Research on genre analysis has generally held a central role in contemporaneous linguistics with the aim of improving professional and academic communication. This study furthers our previous research on a particular genre analysis of the ‘About Us’ site in banks’ corporate websites (Casañ-Pitarch, 2015). In this previous research, a possible standard model of the sections forming this genre was suggested. As result, that research has led to the need for conducting more in-deep studies on other individual elements concerning both the macro and microstructure within the same target genre. The present paper focuses on analysing some features on the use of verbs. To this purpose, the method to analyse the use of verbs is based on classifying verbs following Downing (2014) and to determine the most usual forms of these in each section of the target genre. Results show that the amount and form of verbs in each section are different.